2022
DOI: 10.1002/mnfr.202100944
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Levels Affect the Metabolic Switch of T Cells by Modulating Glucose Uptake and Insulin Receptor Signaling

Abstract: Scope T cell activation requires a metabolic reprogramming from oxidative phosphorylation to aerobic glycolysis to rapidly provide substrates for biosynthesis. An individual's zinc status plays an important role in balancing the activation of T cells and is required for a proper function of immune cells. Furthermore, zinc plays an important role during effector T cell polarization to T helper cell subsets or regulatory T cells, with effector T cells relying on glycolysis and regulatory T cells on oxidative pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…demonstrated a relation between Zn levels and expression of activation marker CD69 in in vitro activated T cells in MLC. [ 30 ] We could not prove that ZS increases CD69 expression in CD3/CD28‐stimulated T cells, but we could show that ZD decreased activation marker expression. Moreover, we could confirm that T cell activation is sensitive to glutaminase inhibition.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…demonstrated a relation between Zn levels and expression of activation marker CD69 in in vitro activated T cells in MLC. [ 30 ] We could not prove that ZS increases CD69 expression in CD3/CD28‐stimulated T cells, but we could show that ZD decreased activation marker expression. Moreover, we could confirm that T cell activation is sensitive to glutaminase inhibition.…”
Section: Discussionmentioning
confidence: 88%
“…In a previous study we have shown that zinc deficiency did not modulate activation marker expression in MLC, whereas ZS caused their upregulation. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While immune function is boosted by a moderate concentration of zinc, it is also suppressed by high doses of zinc. 7 , 8 According to these studies, zinc administration has a potential therapeutic role in graft-versus-host diseases (GVHD) and T cell-mediated autoimmunity. 5 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…While immune function is boosted by a moderate concentration of zinc, it is also suppressed by high doses of zinc. 7,8 According to these studies, zinc administration has a potential therapeutic role in graft-versus-host diseases (GVHD) and T cell-mediated autoimmunity. 5,9 The T helper 17 (Th17) cells are a subtype of CD4 T lymphocytes and are responsible for extracellular pathogen clearance; however, they also cause several autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%